Maternal Prenatal Supplement Intake, but Not Dietary Patterns, Is Associated With Human Milk Microbiota Composition in the CHILD Cohort Study. (7th June 2021) - Chehab, Rana; Fehr, Kelsey; Moossavi, Shirin; Moraes, Theo; Mandhane, Piush; de Souza, Russell; Turvey, Stuart; Subbarao, Padmaja; Khafipour, Ehsan; Azad, Meghan; Forman, Michele
Abstract: Objectives: The human milk microbiome plays an important role in child health and is affected by several factors. We aim to examine whether prenatal diet and supplement intake are associated with human milk microbiota composition. Methods: Among the CHILD Cohort Study members, 771 mothers provided data on diet and supplement intake during pregnancy and a milk sample between 2–6 months postpartum. Maternal diet was assessed using a food frequency questionnaire adapted from the Fred Hutchinson Cancer Center. Three dietary patterns were derived using principal component analysis: plant-based, Western, and balanced. The milk microbiome was analyzed using 16S rRNA gene sequencing. Associations between maternal intake and microbial diversity (Shannon index) and genera relative abundances were examined in R using the Wilcoxon signed-rank test adjusted for multiple comparisons. Results: Maternal supplement intake, but not dietary patterns, was associated with human milk microbiota composition. Approximately 88% of the mothers took prenatal multivitamins. Mothers who took fish oil (18%) or folate supplements (17%) during pregnancy had lower microbial diversity than those who did not (mean ± SD: 1.61 ± 0.64 v. 1.79 ± 0.66 for fish oil [p = 0.01] and 1.64 ± 0.64 v. 1.78 ± 0.67 for folate [ P  = 0.02]). Mothers who took vitamin C supplements (4%), compared to those who did not, had higher microbial diversity (1.99 ± 0.59 v. 1.72 ± 0.65 [ P  = 0.03]) and higher relative abundance of Veillonella but lower abundances of Finegoldia and Stenotrophomonas (pfdr  < 0.05). Compared to the respective supplement non-takers, mothers who took vitamin D supplements (23%) had lower abundance of unclassified Comamonadaceae (pfdr  < 0.05), while mothers who took Ca-containing antacids (11%) had higher abundances of Streptococcus, unclassified Gemellaceae, and Rothia but lower abundances of unclassified Comamonadaceae and unclassified Enterobacteriaceae (pfdr  < 0.05). Conclusions: Human milk microbiota composition differed among mothers who took specific prenatal supplements. Further analysis is needed to explore additional associations while accounting for covariates that impact the human milk microbiome. Funding Sources: CIHR and AllerGen NCE funded the CHILD Cohort Study. The Canadian Lung Association and Canadian Respiratory Research Network funded the milk microbiome sequencing.